Gambaran Tingkat Stres Akademik Mahasiswa DIII Keperawatan Dalam Menjalani Pembelajaran Online di Stikes Kesdam IX/Udayana - Eko Prayitno; Putu Intan Daryaswanti (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2021)
Background: The recent outbreak of the Covid-19 pandemic has restricted activities involving large groups of individuals, including the learning process at institutions that should use an online learning system. Boredom and trouble understanding information during online learning can result in academic stress for students, who must be able to adjust to a new learning method as well as the demands of campus assignments. The goal of this study is to determine the amount of academic stress experienced by DIII nursing students enrolled in online learning at Stikes Kesdam IX/Udayana in 2021. Methods: This study employs a descriptive research method. DIII nursing students from Stikes Kesdam IX/Udayana made up the study's population, which totalled 94 persons. Random sampling with a modified Dass 42 questionnaire was employed in this study with validity value (0.361-0.603) and a reliable value (0.916). Results: According to the findings of the survey, as many as 37 people (50%) aged 17 to 25 years faced significant academic stress. As many as 25 people were found to be suffering from significant academic stress among male respondents (54.3%). On the other hand, students in their junior and senior years were more likely to feel significant academic stress, with up to 22 people reporting this occurrence (53.6%). Meanwhile, 35 students (49.3%) faced extreme academic stress as they had an accomplishment index score of 2.76-3.5. Conclusion: The amount of academic stress experienced by DIII nursing students enrolled in online learning at Stikes Kesdam IX/Udayana, with 94 responses, fell into the severe academic stress group, with as many as 48 people experiencing severe academic stress (51.1% ).